Caracterización de Sistemas Agroforestales Comúnmente Asociados al Cultivo de Cacao en la zona de Febres Cordero, provincia de Los Ríos - Coello Arechúa, María José (2012)
Febres Cordero area is located in the province of the rivers located southeast of Canton Babahoyo. The overall objective of this study was to Characterize cacao agroforestry systems of the farms in the area. The specific objectives were: 1). Participatory diagnostics cocoa producers in the area of Febres Cordero to know the current status of productive, social and economic, 2). Morphologically characterize the types of cocoa under agroforestry systems in the area of study, 3). To quantify the richness and abundance of species present in cocoa, 4). Evaluate the performance of cocoa under the existing agroforestry systems. 5). Benefit of the producer cocoa agroforestry system. In the present investigation with the use of participatory assessment tools was established that the biggest problem is the low production and lack of credit to improve their farms. Ecotypes were characterized 15 of which came from farms in the area and 10 clones witnesses: National (TSE-19, EET-95, EET-96, TSE-103), SIL-6 (TSE-332), SCA-6 ( TSE-11), SCA-12 (TSE-110), IMC-67 (TSE-116), ICS-95 (TSE-111), and the CCN-51, Experimental Station of the South Coast (EELS) and Pichilingue Experiment Station (EETP) INIAP, and morphological data recorded on fruits, seeds, flowers and leaves. Statistical analysis was performed based on Principal Component Analysis, Testing significance of Duncan, Cluster Analysis, Correlation Analysis. The principal component analysis established that the qualitative discriminant variables in this study were: roughness cob, leaf shape and angle baseline.